Anti fungal effect of Echinophora platyloba extract on some common dermathophytes - M Avijgan; M Saadat; MR Nilfrooshzadeh; M Hafizi (Institue of Medicinal Plants, ACECR, 2006)
Objective: Increasing usage of medicinal plants for trapeutic purposes, made a unique place for this branch of complementary medicine. While Echinophora Platyloba has a folkloric usage, unfortunately has not yet reached an eligible palce. This study conducted to evaluate the effect of extract of Echinophora Platyloba on some common dermatophytes. Methods: 4 tubes containing diluted solutions of hydroalcoholic extract (35, 50, 150 and 250 mg/ml) have been prepared and one tube of 0 mg/mL as control hydroalcoholic. Using agar dilution method, fugi were coincubated with diluted solutions of the extract and the growth results were recorded after 21 days. Results: Trichophyton (T) schenlaini and T. verucosum were totally sensitive. T. rubrum and Microsporum (M) gypsum were totally resistant. T. mentagrophyte, M. canis and Epidermophyton flucosum were resistant to 35, 50 and 150 mg/ml dilutions, but they were sensitive to 250 mg/ml. T. violaseum was resistant in 35 and 50 mg/ml but sensitive to 150 and 250 mg/ml. Conclusion: 3 concentrations of hydroalcohalic extract (35, 50 and 150 mg/ml) may have clinical application. On the base of this study, the plant in the mentioned dilutions showed anti fungal effect against T. schoenlieinii, T. verucosum. The plant extract showed weaker antifuongal against T. mentagrophytes, Microsporum canis and Epidermophyton flocusm but this may have not good anti fungal effect aginst T. rubrum and T. gypseum. The next step of study may be the production of drug product and clinical assay.